2014
DOI: 10.1371/journal.pone.0097649
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Glutamate Transporter Subtypes by Pro-Inflammatory Cytokine TNF-α in Cortical Astrocytes from a Rat Model of Amyotrophic Lateral Sclerosis

Abstract: Dysregulation of the astroglial glutamate transporters GLAST and GLT-1 has been implicated in several neurodegenerative disorders, including amyotrophic lateral sclerosis (ALS) where a loss of GLT-1 protein expression and activity is reported. Furthermore, the two principal C-terminal splice variants of GLT-1 (namely GLT-1a and GLT-1b) show altered expression ratio in animal models of this disease. Considering the putative link between inflammation and excitotoxicity, we have here characterized the influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 45 publications
4
17
0
Order By: Relevance
“…Indeed, deficient glutamate clearance has been reported in synaptosomes prepared from several affected brain structures and spinal cords derived from sporadic ALS patients (Rothstein, Martin, & Kuncl, 1992;Grosskreutz, Van Den Bosch, & Keller, 2010). Earlier publications from our group (Dumont, Goursaud, Desmet, & Hermans, 2014;Goursaud, Maloteaux, & Hermans, 2009) and the present results also support such suggestions by showing a reduced aspartate uptake velocity in hSOD1 G93A astrocytes. the human equivalent of GLT-1), as has been observed in the motor cortex and spinal cord of familial and sporadic ALS patients (Rothstein, Van, Levey, Martin, & Kuncl, 1995;Fray et al, 1998;Grosskreutz et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, deficient glutamate clearance has been reported in synaptosomes prepared from several affected brain structures and spinal cords derived from sporadic ALS patients (Rothstein, Martin, & Kuncl, 1992;Grosskreutz, Van Den Bosch, & Keller, 2010). Earlier publications from our group (Dumont, Goursaud, Desmet, & Hermans, 2014;Goursaud, Maloteaux, & Hermans, 2009) and the present results also support such suggestions by showing a reduced aspartate uptake velocity in hSOD1 G93A astrocytes. the human equivalent of GLT-1), as has been observed in the motor cortex and spinal cord of familial and sporadic ALS patients (Rothstein, Van, Levey, Martin, & Kuncl, 1995;Fray et al, 1998;Grosskreutz et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Astrocyte uptake of glutamate not only reduces the extracellular levels but can also induce astrocyte reactivity and alter multiple astrocyte functions (Morales & Rodriguez, 2012), so it is important to examine astrocyte-mediated glutamate uptake. Interestingly, proinflammatory cytokines, such as TNFα, decrease the expression of glutamate transporters, especially GLAST (Dumont, Goursaud, Desmet, & Hermans, 2014). Therefore, we used radiolabeled glutamate to determine whether rPK2 treatment could increase glutamate uptake by primary mouse astrocytes.…”
Section: Pk2 Overexpression Reduces Total Number Of Astrocyte Procementioning
confidence: 99%
“…Patients with ALS have been reported to have impaired glutamate metabolism, caused by reduced glutamate uptake by astrocyte-associated glutamate transporters (Rothstein et al, 1992). A recent study found that the inflammatory cytokine TNF-α is able to increase the expression of GLT-1 in astrocytes cultured from wild-type rats, but not those cultured from a rat model of ALS (Dumont et al, 2014). Another study has linked astrocytes, inflammation, and ALS pathology, reporting that in both mouse and human ALS, astrocytes have upregulated expression of the anti-inflammatory cytokine transforming growth factor-β1 (TGF-β1), which prevents microglial and T cell production of IGF-1, leading to accelerated disease progression due to the loss of inflammatory-mediated neuroprotection (Endo et al, 2015).…”
Section: Astrocytes In Neuropathologiesmentioning
confidence: 99%